Navigation Aid for Visually Impaired Persons using Vibration Haptics on a Jacket-cum-Headband Setup - Aditya Iyer (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The device proposed here is a jacket-cum-headband device for mapping chaotic environments and communicating locations of obstacles to visually impaired persons. This project focuses on constructing a device which uses vibration as a haptic mode of communication to inform users on potential obstacles in their vicinity. This device is a low-cost solution for visually impaired persons to navigate within chaotic indoor environments such as houses, schools, or workplaces. The device is manufactured using 3D printed parts and readily available electronics, mounted onto articles of clothing for ease of use. The device is equipped with a Raspberry Pi 4B microcontroller, a USB colour camera, and 3 vibration-haptic modules embedded within a wearable shirt. The device uses Convolution Neural Networks (CNNs) and mathematical estimation formulas to detect obstacles in the user’s proximity and determine their distance and direction from the user. The device communicates the locations of potentially hazardous obstacles to the user by inducing vibrations of varied intensity in the vibration-haptic modules. The device is tested on 4 different objects located in front of, to the left of, and to the right of the user, at distances between 1 metre and 6 metre.
Keywords: Navigation Aid; Raspberry Pi; CNN Algorithm; Object Detection; Visually Impaired